Legal Consequences of Amendment And/Or Implementation of Homologation Outside Court Authorization - Panjaitan, Wijaya Natalia; Nababan, Frandy Septior (Fakultas Hukum Universitas Pattimura, 2023)
The composition of Homologation that has been approved is ratified and decided by the court. But the problem is when composition that have been agreed and have been validated are then changed for certain interests so that the contents are no longer the same that has been validated. The purpose of this study is to find out how the legal consequences of amendments and/or the implementation of homologation outside the court. This study case uses a normative juridical method by using a statutory, case approach, and conceptual approach. Homologation composition through Suspension of Obligation for Payment and Bankruptcy have been regulated, so when there is a change and/or implementation of a composition agreement passed by the court (Homologation) outside the court, it is invalid.